Improved respiratory motion tracking through a novel fiducial marker placement guidance system during electromagnetic navigational bronchoscopy (ENB) - Hayley Stowe; Stella Ogake; Sunil Sharma; Suzanne Kelly; Morgan McDonald; Kayla Stanley; Paul Walker; Hyder Arastu; Carlos Anciano Granadillo; Mark Bowling; Andrew Ju (Radiation Oncology, 2019)
Abstract Background Stereotactic ablative radiotherapy (SABR) is a treatment option for patients with early stage non-small cell lung cancer (NSCLC) and recurrent or oligometastatic disease who are not surgical candidates. Due to the continuous motion of tumors within the lungs, implementing a strategy to track the target lesion is crucial. One method is to place fiducial markers which the robotic SABR system is able to track during treatment. However, placing these markers in a manner that maximizes tracking efficacy can be challenging. Using a novel fiducial placement guidance system (FPGS) during fiducial deployment may offer a way to improve the quantity of fiducials tracked by the robotic SABR system. Method This was an institutional, retrospective review identifying all patients who received robotic SABR for lung tumors from May 2015 until January 2017. The FPGS was instituted in May 2016. The median number of fiducials tracked and the rate of complication was compared between patients whose fiducials were placed using FPGS versus those that were not. Results A total of 128 patients with 147 treated lung lesions were identified. Of the lesions that utilized FPGS (n = 44), 28 had 2 tracked fiducials (63.6%), 14 had 3 (31.8%) and 2 had 4 (4.6%). Of the lesions treated without FPGS (n = 103), 5 had 1 tracked fiducial (4.9%), 91 had 2 (88.4%), 6 had 3 (5.8%), and 2 had 4 (1.9%). A significant improvement in the median number of fiducials tracked per fraction was observed for the lesions with fiducials placed using FPGS on Wilcoxon rank sum test (p < 0.001). The rate of complication was low and not statistically different between cohorts (p = 0.44). Conclusions The FPGS can be used during the deployment of fiducial markers and may increase the number of fiducials tracked. Trial registration An exemption for this retrospective review was granted by the East Carolina University IRB under UMCIRB 15-001726.